Brand psychology consumer perceptions, corporate reputations - Gabay, Jonathan (London Kogan Page, 2015)
"Revealing the hidden processes behind why certain brands command our loyalty and trust, Brand Psychology looks at how to build up a positive brand image through Corporate Social Responsibility and ethical transparency. Reputation management authority Jonathan Gabay takes readers on a tour of the corporate, political and personal brands whose understanding of consumer psychology has either built or broken them, with examples such as e-cigarette legislation, the London 2012 Olympics, the iPhone 5S's fingerprint ID technology and Miley Cyrus.He answers key questions about brand and reputation management, including: --Why do we trust some brands more than others? --How important is integrity for a brand's survival? --How can brand confidence be rebuilt during a crisis? Combining practical, how-to advice on media relationships and crisis management, with an exploration of reputation psychology and consumer motivation. Brand Psychology reveals how to build a meaningful brand that resonates with the public"-- Provided by publisher.
"Why do we trust some brands more than others? How important is integrity for a brand's survival? How can brand confidence be rebuilt during a crisis? Using both new and classic insights from social psychology, cognitive psychology and neuroscience, Brand Psychology reveals the hidden processes behind why certain brands command our loyalty, trust and - most importantly - disposable income. Reputation management authority Jonathan Gabay takes readers on a tour of the corporate, political, and personal brands whose understanding of consumer psychology has either built or broken them. Suitable for marketing, branding and PR professionals, reputation management specialists and students, Brand Psychology takes examples from e-cigarette legislation, the iPhone 5S's fingerprint ID technology, Barclays' branded bikes and the London 2012 Olympics, Miley Cyrus and the UK National Health Service's big data to reveal how to build a meaningful brand that resonates with the public"-- Provided by publisher.
Left Lobe -- Chapter 1: Introduction -- Chapter 2: Lies, excuses and further justifications for inconvenient truths -- Chapter 3: Brains, brands, bytes and Bolshevik brawls -- Chapter 4: Getting to know you - from reputation in the cloud to big data on chips -- Chapter 5: Smoke and mirroring -- Chapter 6: Rings of confidence -- Chapter 7: Egg whites, white wash and Snow flakes -- Chapter 8: Flattered trusted minds and fluttery trusting hearts -- Chapter 9: Under the influence -- Chapter 10: Believing is not seeing. Seeing is believing -- Chapter 11: From addictive self-interest to interesting selves -- Chapter 12: Brand me -- Chapter 13: Maslow - misunderstood? -- Chapter 14: The Church of Brand Ideology: open for redemption, 24/7Right Lobe -- Chapter 15: In the spotlight -- Chapter 16: Can we still be friends? -- Chapter 17: Oh Lord it's hard to be humble when you're perfect in every way -- Chapter 18: The cold-hearted wolf thrives on warm-blooded sheep -- Chapter 19: Big boys don't cry -- Chapter 20: The authentic employer brand -- Chapter 21: Brand stories - tell, don't yell -- Chapter 22: Rhetoric rules reasoning -- Chapter 23: The final question first.
Includes bibliographical references and index.
Keywords: Branding (Marketing) -- Psychological aspects; Brand name products -- Psychological aspects; Customer loyalty; Corporate image